Умови та принципи реалізації захисту права на житло в Україні - Чайковський, О. І.; Chaikovskyi, O. I. (Одеса : Гельветика, 2021)
Житлове питання є надзвичайно гострим для України, а захист права на житло є одним зі способів реалізації права на житло, передбаченого Конституцією України. Право на житло закріплено статтею 47 Конституції України. Вона передбачає, що кожен мешканець України може побудувати житло, придбати його у власність або взяти в оренду. Проте, реалізуючи своє право на житло, громадяни України де дальше стикаються з проблемою його захисту. Одним із важливих показників забезпечення житлових прав та законних інтересів громадян є гарантованість захисту прав і законних інтересів як наймачів, так і власників житла. Це право охороняється Конституцією як актом найвищої юридичної сили та відповідними законами України. При цьому обов’язок забезпечення житлом усіх бажаючих на державу вже не покладається. Держава повинна створювати лише умови для реалізації громадянином своїх конституційних прав, а саме: створювати можливості для підвищення життєвого рівня своїх громадян, щоб кожен мав можливість придбати житло у власність або в оренду; сприяти розвитку ринку житла; підвищувати добробут населення тощо. Держава зобов’язана надати житло лише громадянам, які потребують соціального захисту. Окрім того, держава забезпечує стабільність правовідносин у житловій сфері. Конституція закріплює принцип, за яким право приватної власності на житло є непорушним. Тому право на житло як одна з форм забезпечення природніх потреб громадян охороняється законом, а в разі його порушення виникає право на захист. Саме держава повинна вживати різних заходів для того, щоб ніхто не був примусово позбавлений житла, інакше як на підставі закону за рішенням суду. Достатній життєвий рівень для громадянина і його сім’ї включає також харчування, одяг і житло, а головне – закріплюється право кожного на неухильне поліпшення умов життя. Тобто наявність житла є достатнім життєвим рівнем, що визнається також статтею 25 Загальної декларації прав людини.

The housing problem is extremely acute in Ukraine, and protection of the right to housing is one of the methods of exercising the right to housing recognized in the Constitution of Ukraine. The right to housing is enshrined in Article 47 of the Constitution of Ukraine, which states that every resident of Ukraine can build, purchase or rent housing. However, when exercising their right to housing Ukrainian citizens increasingly face the problem of protecting this right. One of the important indicators of ensuring the housing rights and lawful interests of citizens is the guaranteed protection of the rights and lawful interests of both tenants and owners of housing. This right is guaranteed by the Constitution as an act of the supreme legal force, and by the relevant laws of Ukraine. At the same time, the government is no longer obliged to provide housing to everyone. The government is only required to create conditions enabling citizens to exercise their constitutional rights, in particular: create opportunities for its citizens to raise their living standards, to make sure that everyone is able to purchase or rent housing; promote development of the housing market; raise wellbeing of the population, etc. The government is obliged to provide housing only to the citizens who need social protection. In addition, the government is responsible for ensuring stability of legal relationships in the housing sector. The Constitution sets forth the principle saying that the private ownership of housing is inviolable. Therefore, the right to housing as one of the forms of fulfilling natural needs of citizens is protected by law, and violation of this right invokes the right to protection. The government must take various measures to make sure that nobody is forcibly deprived of housing other than in a lawful manner under a court ruling. Sufficient standards of living for a citizen and their family include, inter alia, food, clothing and housing, and most importantly, the guaranteed right of everyone to a continuous improvement of living conditions. In other words, the availability of housing is a sufficient standard of living, which is also recognized in Article 25 of the Universal Declaration of Human Rights.
Чайковський О. І. Умови та принципи реалізації захисту права на житло в Україні / О. І. Чайковський // Юридичний вісник. - Одеса : Гельветика - 2021. - № 3. - С. 156-162.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; право на житло; право власності на житло; нерухоме майно; захист права на житло; умови захисту житла; right to housing; housing ownership right; immovable property; protection of the right to housing; conditions for protection of housing